Preparation method of single-atom glucose electrochemical working electrode

By combining a single-atom catalyst with carbon nanotubes, a single-atom glucose electrochemical working electrode can quickly and accurately detect glucose at low voltages is prepared, which solves the problems of high working voltage and interfering substances in the prior art, and achieves a good detection effect under low oxygen conditions.

CN115856050BActive Publication Date: 2025-04-18MINKANG MEDICAL TECH (TIANJIN) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202211554505.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-06
Publication Date
2025-04-18
Estimated Expiration
2042-12-06

AI Technical Summary

Technical Problem

The existing glucose electrochemical working electrodes have high working voltages and interfering substances, resulting in low accuracy of glucose detection, especially under low oxygen conditions.

Method used

A single-atom catalyst is used to combine with carbon nanotubes, and a single-atom glucose electrochemical working electrode is formed by combining carbon nanotube pyridation modification, quaternization modification and carboxylic activation, which can quickly and accurately detect glucose at low voltage.

Benefits of technology

The specific detection of glucose at low operating voltage is achieved, the influence of interfering substances is reduced, and the good linear response is shown under low oxygen conditions, overcoming the shortcomings of the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115856050B_ABST
    Figure CN115856050B_ABST
Patent Text Reader

Abstract

The preparation method of the single-atom glucose electrochemical working electrode of the present invention comprises: pyridyl modification of carbon nanotubes; quaternary ammonium modification of carbon nanotubes and carboxyl activation; synthesis of single-atom catalysts; preparation of glucose electrochemical working electrode, dispersing purified single-atom catalysts in water to obtain 9-11 mg / mL of purified single-atom catalyst aqueous dispersion, mixing 9-11 μL of purified single-atom catalyst aqueous dispersion, 6-8 μL of 9-11 mg / mL glucose oxidase aqueous solution, 1.5-1.8 μL of 9-11 mg / mL cross-linking agent aqueous solution and 30-32 μL of water, treating with ultrasound for 20-40 minutes, and cross-linking at room temperature for 50-70 minutes to obtain a sensing layer modification solution; dripping the sensing layer modification solution onto the electrode surface, placing the electrode in a 34-37°C constant temperature and humidity incubator for 18-24 hours to obtain a working electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of single-atom catalysts, relates to the application of single-atom catalysts in the field of glucose electrochemical sensing, and particularly relates to a method for preparing a single-atom glucose electrochemical working electrode. Background Art

[0002] Diabetes is a metabolic disease characterized by persistent high blood sugar levels. It has become a global public health problem. According to the latest data from the International Diabetes Federation, there are 537 million diabetics in the world, and almost one in ten adults has diabetes. Diabetes can induce a variety of complications such as coronary heart disease, peripheral neuropathy, and diabetic foot, and has become a major killer threatening human life and health.

[0003] So far, there is no cure for diabetes. The most effective clinical monitoring method is to monitor the glucose concentration in the patient's blood in real time and maintain the blood glucose concentration within the normal range. Blood glucose monitoring data is the basis for formulating treatment plans for diabetic patients, and is also an important indicator for evaluating the effectiveness of treatment. It can also detect hypoglycemia in patients in a timely manner, thereby preventing the occurrence of acute accidents. Therefore, the development of glucose sensing technology for blood glucose monitoring is of vital importance in the detection and treatment of diseases such as diabetes.

[0004] At present, the main methods for blood glucose monitoring include optical method, colorimetric method, energy metabolism method and electrochemical method. Among them, the electrochemical method is widely used in glucose working electrodes due to its high sensitivity, fast response and simple operation. The electrochemical method has a fast response time and a wide detection range. The measured electrochemical signal can be converted into the corresponding glucose concentration, which can well realize the quantitative analysis of glucose concentration.

[0005] However, there are also some problems with the existing glucose electrochemical working electrodes, mainly reflected in: 1. The working voltage is high, and interfering substances in the body will be oxidized at a higher voltage, which has a great impact on the accuracy of glucose detection; 2. Glucose oxidase can specifically oxidize glucose into gluconolactone. Under normal circumstances, oxygen participates in the reaction as the electron acceptor of glucose oxidase, but the oxygen concentration in the tissue fluid is very low, which will lead to inaccurate test results.

[0006] Chinese patent CN202010246108.4 discloses a working electrode of a glucose monitoring probe, which has: a base layer, which is arranged on a flexible substrate; a sensing layer, which is formed on the base layer by coating a sensing layer reagent, and can react chemically with glucose in blood or tissue fluid, and the sensing layer reagent includes a metal polymer, glucose enzyme, carbon nanotubes and a cross-linking agent, the carbon nanotubes adsorb the metal polymer and the glucose enzyme, and add amino modifications to the carbon nanotubes so that the metal polymer and the carbon nanotubes are tightly covalently bonded and combined with the glucose enzyme; a semipermeable membrane, which is formed on the sensing layer to control the passing rate of glucose molecules; and a biocompatible membrane, which is formed on the semipermeable membrane. According to the present disclosure, the working voltage of the working electrode can be reduced, interference can be reduced, the service life of the glucose monitoring probe can be extended, and the sensitivity to glucose can be improved.

[0007] Its disadvantages: In the sensing layer reagent of the patent, the amino-modified carbon nanotubes react with metal redox polymers, glucose oxidase and crosslinkers by covalent bonding. The metal redox polymers include polyvinylferrocene, quaternized poly(4-vinylpyridine) of potassium ferrocyanide, quaternized poly(1-vinylpyridine) of potassium ferrocyanide, quaternized poly(4-vinylpyridine) of ferrocyanide, quaternized poly(1-vinylimidazole) of ferrocyanide, osmium 2,2'-bipyridine complex coordinated to poly(1-vinylpyridine), osmium 2,2'-bipyridine complex coordinated to poly(4-vinylpyridine), cobalt 2,2'-bipyridine complex coordinated to poly(1-vinylpyridine), and cobalt 2,2'-bipyridine complex coordinated to poly(4-vinylpyridine). This type of metal redox polymer has many disadvantages: 1) The oxidation peak potentials of ferrocene, potassium ferrocyanide group, osmium 2,2'-bipyridine complex, and cobalt 2,2'-bipyridine complex are all higher than 0.2V. At this potential, interfering substances such as ascorbic acid and uric acid will still undergo redox reactions, interfering with the accuracy of glucose monitoring. 2) The above transition metal complexes are directly coordinated with the polymer, and there is no carbon-hydrogen chain in the middle as a connection, which will greatly reduce the electron transfer rate between the metal complex and the enzyme, affecting the sensitivity and detection stability.

[0008] Chinese patent CN202010832447.0 discloses a glucose electrochemical sensor based on a cationic redox polymer hydrogel containing a transition metal complex medium, and a preparation method thereof. The sensing layer of the glucose electrochemical sensor includes a cationic redox polymer containing a transition metal complex medium, glucose oxidase and a cross-linking agent. The glucose electrochemical sensor of the present invention can specifically detect glucose, and its stable current signal has a high linear correlation coefficient with the glucose concentration; it can eliminate the influence of interfering substances on glucose detection; it can also eliminate the influence of oxygen concentration in the solution on glucose detection.

[0009] Its disadvantages: The metal site (M) of the cationic redox polymer of the transition metal complex provided by the patent coordinates with the N element of the biimidazole and bipyridine derivatives to form an M-N5 structure, which is not as stable as M-N6 and has a significant gap in electron transfer efficiency compared to M-N6. Figure 1 It can be clearly seen that the redox peak of the cationic redox polymer is around 0.2 V. At this potential, interfering substances such as ascorbic acid and uric acid will still undergo redox reactions, which will interfere with the accuracy of glucose monitoring.

[0010] U.S. Patent No. 7,090,756 discloses several novel transition metal (Fe, Co, Ru, Os, V) complexes. Transition metal complexes can act as redox mediators in enzyme-based electrochemical sensors. They can efficiently accept or provide electrons to enzymes and quickly exchange electrons with sensors. The ligands of the transition metal complexes include at least one substituted or unsubstituted biimidazole ligand, and may further include a second substituted or unsubstituted biimidazole ligand or a bipyridine or pyridyl imidazole ligand. The patent also discloses that the transition metal is covalently linked to the polymer backbone.

[0011] Its disadvantages: The polymer skeletons disclosed in the patent include poly(4-vinylpyridine), poly(N-vinylpyridine), polyalanine, polyethylene / maleic anhydride copolymer, methyl vinyl ether / acrylic anhydride copolymer, polyethylene diphenylethylene, polypropylamine, polylysine, carboxypolyvinylpyridine and poly(sodium 4-styrene sulfonate). There are many disadvantages in using these polymer skeletons: 1) polymer synthesis and purification are difficult; 2) polymer and transition metal covalent bonding process load; 3) this type of polymer does not have the function of electron transfer, which will affect the electron transfer efficiency between enzyme and electrode.

[0012] In view of the understanding of relevant background issues, the present invention provides a single-atom glucose electrochemical working electrode and a preparation method thereof.

[0013] Compared with the above patents, the preparation of this patent is simpler in structure and avoids the participation of high molecular polymers. From a structural analysis: Chinese patent CN202010246108.4 (silicon-based) is a high molecular polymer connected to a transition metal complex to form a metal-N5, and then amino-modified carbon nanotubes are added to assist electron transfer; Chinese patent CN202010832447.0 (Microtech) is a high molecular polymer connected to a transition metal complex metal-N5; U.S. Patent US7,090,756 (Abbott) is a high molecular polymer connected to a transition metal complex metal N6. The above patents have continuous transition metal complex active sites connected to high molecular polymers, while this patent directly uses carbon nanotubes as carriers and connects to single atom sites, avoiding the introduction of high molecular polymers, making the preparation simpler and the structure clearer.

[0014] The single-atom glucose electrochemical working electrode provided by the present invention can specifically detect glucose, can detect glucose at a low working voltage, and can eliminate the influence of interfering substances on glucose detection; it shows a good linear relationship for different glucose concentrations under hypoxic conditions, and can eliminate the influence of oxygen concentration in the solution on glucose detection, thereby overcoming the shortcomings of the prior art.

[0015] Therefore, the glucose electrochemical working electrode based on the single-atom catalyst of the present invention has a wide range of application value in continuous blood glucose detection. Summary of the invention

[0016] The present invention relates to a method for preparing a single-atom glucose electrochemical working electrode based on a single-atom catalyst. The electrochemical working electrode provided by the present invention can continuously detect glucose concentration rapidly and accurately in a low-voltage, oxygen-deficient environment.

[0017] In order to achieve the above object, the present invention adopts the following technical solutions:

[0018] A method for preparing a single-atom glucose electrochemical working electrode of the present invention comprises the following steps:

[0019] (I) Pyridylation of carbon nanotubes

[0020] (a) Purification of carbon nanotubes (CNTs)

[0021] First, the carbon nanotubes are dispersed in a concentrated hydrochloric acid solution with a concentration of 8-12 mol / L and soaked for 18-30 hours, and then refluxed in the concentrated hydrochloric acid solution for 4-6 hours, and then the carbon nanotubes are washed with water, ethanol and acetone in sequence until the pH of the washing solution is 7, and then the obtained solid is dried in a vacuum drying oven at a vacuum degree of -0.1 MPa and a temperature of 70°C for 18-30 hours to obtain purified carbon nanotubes (CNT);

[0022] (b) Preparation of diazonium salt

[0023] Dissolve 1 part of sodium nitrite in 1.5-2 parts of water, and dissolve 1-1.5 parts of 4-aminopyridine in 1-1.2 parts of 3-5 mol / L hydrochloric acid, then mix the two solutions in an ice water bath and stir for 30-60 minutes to obtain a mixed solution of sodium nitrite and 4-aminopyridine;

[0024] (c) Carbon nanotube pyridyl modification (CNT-py)

[0025] 90-110 mg of the purified carbon nanotubes in step (a) are dispersed in 190-210 mL of N,N-dimethylformamide (DMF), and dispersed under ultrasound for 50-150 min to obtain a solution of purified carbon nanotubes. The purified carbon nanotube solution is then cooled to 0°C, and then 11-15 ml of a mixed solution of sodium nitrite and 4-aminopyridine obtained in step (b) is added dropwise to the purified carbon nanotube solution, first stirred at 0°C for 2-4 h, then stirred at room temperature for 12-16 h, filtered and collected, and then washed with 2 mol / L hydrochloric acid, 2 mol / L sodium hydroxide, water and acetone in sequence to remove impurities on the obtained product, so that the pH of the washing solution is 7, and finally the solid obtained after washing is placed in a vacuum drying oven with a vacuum degree of -0.1 MPa, and dried at 70°C for 18 to 30 h to obtain pyridine-modified carbon nanotubes (CNT-py);

[0026] (II) Quaternization modification of carbon nanotubes and carboxyl activation

[0027] (d) Carbon nanotube quaternization (CNT-py-BHA)

[0028] Take 75-80 mg of pyridine-modified carbon nanotubes (CNT-py) obtained in the above step (c), add 1.8-2.2 mL of anhydrous N, N-dimethylformamide (DMF) thereto for ultrasonic dispersion, then add 20-25 mg of 6-bromohexanoic acid (6-BHA), stir the solution at 90° C. for 20-26 h, after the solution is cooled to room temperature, slowly pour it into 18-22 mL of ethyl acetate solution and stir rapidly, filter to obtain a solid, and dry the solid at 70° C. for 18 to 30 h in a vacuum drying oven with a vacuum degree of -0.1 MPa to obtain quaternary ammonium-modified carbon nanotubes (CNT-py-BHA);

[0029] (e) Carboxyl activation of carbon nanotubes

[0030] Take 50-52 mg of the quaternized carbon nanotubes (CNT-py-BHA) obtained in the above step (d), add them to 1.8-2.2 mL of anhydrous N,N-dimethylformamide (DMF) for ultrasonic dispersion, and then add 17.5-19 mg of N,N,N',N'-tetramethyl-O-(N-succinimidyl) urea tetrafluoroborate (TSTU) to obtain a suspension, stir the suspension for 10-20 min, then add 8-12 μL of N,N-diisopropylethylamine, and stir the obtained solution for 7-9 h to obtain a solution in which the carbon nanotube carboxyl group is activated;

[0031] in:

[0032] (III) Synthesis of single atom catalysts

[0033] (f) Synthesis of single-atom site Os-N6 metal precursor

[0034] 320-330 mg of N,N'-dimethyl-2,2'-biimidazole and 430-440 mg of (NH4)2OsCl6 were poured into 11-13 mL of ethylene glycol solution respectively, and stirred at 135-145°C for 22-26 h under nitrogen protection to obtain a reaction mixture; 270-278 mg of N-(6-aminohexyl)-N'-methyl-2,2'-biimidazole was dissolved in 2.5-3.5 mL of ethylene glycol, and the solution was introduced into the above reaction mixture with a syringe, and heated and stirred at 160°C for 20-26 h under nitrogen protection to obtain a mixture, and the above mixture was cooled to room temperature and passed through a vacuum evaporator. The precipitate is removed by filtration to obtain a filtrate, and the filtrate is diluted with 55-65 mL of water, and then mixed with 11-13 mL of AG1×4 resin chloride, and the mixture is stirred in an exposed conical flask for 40-50 hours to completely oxidize the Os(Ⅱ) complex to the Os(Ⅲ) complex, and the solution after the reaction is slowly poured into the NH4PF6 solution and stirred rapidly, and then the precipitate is collected by suction filtration through a sintering funnel to obtain a crude product, and the crude product is ultrasonically dissolved again in 8-12 mL of acetonitrile, and centrifuged to obtain a clear liquid, and the obtained clear liquid is added to the NH4PF6 solution, and the NH4PF6 solution is prepared by dissolving 1.0-1.1 g of NH4PF6 in 50 mL of water. After the precipitate is generated again, the precipitate is collected by suction filtration, and then washed with pure water to obtain a solid, and the solid is dried in a vacuum drying oven with a vacuum degree of -0.1 MPa at a temperature of 70°C for 20-26 hours to obtain a single-atom site Os-N6 metal precursor;

[0035] (g) Synthesis of single atom catalysts

[0036] Take 320-340 mg of the single-atom site Os-N6 metal precursor in step (f), slowly add it to the carbon nanotube carboxyl activated solution in step (e), and then add 35-45 μL of N, N-diisopropylethylamine, stir the mixture at room temperature for 20-26 hours, filter it, wash the obtained precipitate with deionized water until the filtrate is colorless, and dry the washed precipitate in a vacuum drying oven with a vacuum degree of -0.1 MPa at a temperature of 70°C for 20-26 hours to obtain a single atom catalyst;

[0037] (h) Purification of single atom catalysts

[0038] The single atom catalyst obtained in step (g) is dissolved in 18-22 mL of water, and then mixed with 3-5 mL of AG1×4 chloride resin, stirred in a beaker for 22-26 h, filtered to remove the resin, and rotary evaporated to obtain (CNT-Os6N) solid, which is dried at a temperature of 68-72° C. for 20-25 h to obtain a purified single atom catalyst;

[0039] (IV) Preparation of Glucose Electrochemical Working Electrode

[0040] (i) Preparation of sensor layer modification solution

[0041] The purified single-atom catalyst obtained in step (h) is dissolved in water to obtain a 9-11 mg / mL aqueous solution of the purified single-atom catalyst, 9-11 μL of the aqueous solution of the purified single-atom catalyst, 6-8 μL of a 9-11 mg / mL aqueous solution of glucose oxidase, 1.5-1.8 μL of a 9-11 mg / mL aqueous solution of polyethylene glycol diglycidyl ether, and 30-32 μL of water are mixed, and the mixture is treated with ultrasound for 20-40 min, and then cross-linked at room temperature for 50-70 min to obtain a sensing layer modification solution;

[0042] (j) Electrode surface modification

[0043] The sensing layer modification solution is dropped onto the electrode surface. After the surface of the electrode is fully covered, the electrode is placed in a constant temperature and humidity incubator at 34-37° C. for 18-24 hours to obtain a working electrode.

[0044] The method for preparing the single-atom glucose electrochemical working electrode of the present invention comprises the following steps: the ultrasonic wave is produced by an ultrasonic cleaning machine operating at a frequency of 40 KHz.

[0045] The preparation method of the single-atom glucose electrochemical working electrode of the present invention comprises the following steps: the working electrode is scanned in a buffer solution at a scanning rate of 20mV / s, 50mV / s, 100mV / s, 200mV / s, 300mV / s, 400mV / s or 500mV / s to obtain a cyclic voltammetry curve; below -200mV, the redox peak of the electrode is lower than the voltage required for the catalytic oxidation of interfering substances such as ascorbic acid, uric acid and acetaminophen, and the electrode has good anti-interference ability.

[0046] The preparation method of the single-atom glucose electrochemical working electrode of the present invention comprises: placing the working electrode in 2mM, 5mM, 8mM, 11mM, 15mM, 20mM, 25mM and 30mM concentration glucose solutions respectively, recording the current signal of the working electrode, and the linear relationship coefficient R between the current signal and the glucose concentration 2 It is 0.99, indicating that the working electrode has a good linear response to glucose concentration.

[0047] A single-atom glucose electrochemical working electrode is prepared by using the preparation method of the single-atom glucose electrochemical working electrode.

[0048] The preparation method of the single-atom glucose electrochemical working electrode of the present invention comprises: placing the working electrode in a 10 mM glucose solution, introducing pure nitrogen and pure oxygen during the test, and observing the change of the current signal. The test results are as follows Figure 4 As shown in the figure, the introduction of pure nitrogen and pure oxygen has little effect on the current signal, which shows that the single-atom glucose electrochemical working electrode is not affected by oxygen deficiency and can meet the application scenario of low oxygen concentration in human tissue fluid.

[0049] The method for preparing the single-atom glucose electrochemical working electrode of the present invention, wherein: the buffer solution is a 1X PBS buffer solution manufactured by Shanghai Bioengineering.

[0050] The single-atom glucose electrochemical working electrode prepared according to the method of the present invention has the following beneficial effects:

[0051] 1. The glucose electrochemical working electrode of the present invention can specifically detect glucose, and its stable current signal has a high linear correlation coefficient with the glucose concentration.

[0052] 2. The working voltage of the glucose electrochemical working electrode of the present invention is low, and the influence of interfering substances on glucose detection can be eliminated.

[0053] 3. The glucose electrochemical working electrode of the present invention can show a good linear relationship with different glucose concentrations under hypoxic conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1Cyclic voltammetry curves of the glucose electrochemical working electrode based on single-atom catalyst in phosphate buffer solution at different scan rates (20mV / s, 50mV / s, 100mV / s, 200mV / s, 300mV / s, 400mV / s, 500mV / s);

[0055] Figure 2 Time-current curves of the glucose electrochemical working electrode based on single-atom catalyst in glucose solutions of different concentrations (2mM, 5mM, 8mM, 11mM, 15mM, 20mM, 25mM, 30mM), where the working electrode voltage is 0.1V;

[0056] Figure 3 Linear relationship between the current signal and glucose concentration of the glucose electrochemical working electrode based on single atom catalyst;

[0057] Figure 4 Time-current curve of glucose electrochemical working electrode based on single-atom catalyst in 10mM glucose PBS solution. During the test, pure nitrogen and pure oxygen were introduced into the solution to observe the change of current signal;

[0058] Figure 5 Schematic diagram of the structure of the polymer-linked transition metal complex produced by Abbott;

[0059] Figure 6 This is a schematic diagram of the structure of the polymer-linked transition metal complex produced by Weitai Company;

[0060] Figure 7 Schematic diagram of the single-atom catalyst structure produced for this patent. DETAILED DESCRIPTION

[0061] In order to further understand the present invention, the single atom catalyst, preparation method and application provided by the present invention are described in detail below in conjunction with the examples. The specific examples described here are only used to explain the present invention and are not used to limit the present invention.

[0062] The method for preparing the single-atom glucose electrochemical working electrode of the present invention comprises the following steps:

[0063] (I) Pyridylation of carbon nanotubes

[0064] (a) Purification of carbon nanotubes (CNTs)

[0065] First, the carbon nanotubes were dispersed in a concentrated hydrochloric acid solution with a concentration of 10 mol / L and soaked for 24 hours, then refluxed in the concentrated hydrochloric acid solution for 5 hours, and then washed with water, ethanol and acetone in turn until the pH of the washing solution was 7, and then the obtained solid was dried in a vacuum drying oven at a vacuum degree of -0.1 MPa and a temperature of 70°C for 24 hours to obtain purified carbon nanotubes (CNT);

[0066] (b) Preparation of diazonium salt

[0067] Dissolve 4.90 g of sodium nitrite in 7 ml of water, and dissolve 6.58 g of 4-aminopyridine in 5 mL of 4 mol / L hydrochloric acid, then mix the two solutions and stir for 30 min in an ice-water bath to obtain a mixed solution of sodium nitrite and 4-aminopyridine;

[0068] (c) Carbon nanotube pyridyl modification (CNT-py)

[0069] 100 mg of the purified carbon nanotubes of step (a) were dispersed in 200 mL of N,N-dimethylformamide (DMF), and dispersed under ultrasound for 100 min to obtain a solution of purified carbon nanotubes. The purified carbon nanotube solution was then cooled to 0°C, and the mixed solution of sodium nitrite and 4-aminopyridine obtained in the above step (b) was added dropwise to the purified carbon nanotube solution, and stirred at 0°C for 3 h, and then stirred at room temperature for 14 h, and the obtained product was filtered and collected, and then washed with 2 mol / L hydrochloric acid, 2 mol / L sodium hydroxide, water and acetone in sequence to remove impurities on the obtained product, so that the pH of the washing solution was 7, and finally the solid obtained after washing was placed in a vacuum drying oven with a vacuum degree of -0.1 MPa, and dried at 70°C for 24 h to obtain pyridine-modified carbon nanotubes (CNT-py);

[0070] (II) Quaternization modification of carbon nanotubes

[0071] (d) Carbon nanotube quaternization (CNT-py-BHA)

[0072] Take 78 mg of pyridine-modified carbon nanotubes (CNT-py) obtained in the above step (c), add 2 mL of anhydrous N, N-dimethylformamide (DMF) thereto for ultrasonic dispersion, then add 22.5 mg of 6-bromohexanoic acid (6-BHA), stir the solution at 90 ° C for 24 h, after the solution is cooled to room temperature, slowly pour it into 20 mL of ethyl acetate solution and stir it quickly, filter to obtain a solid, and dry the solid at a temperature of 70 ° C for 18 to 30 h in a vacuum drying oven with a vacuum degree of -0.1 MPa to obtain quaternary ammonium-modified carbon nanotubes (CNT-py-BHA);

[0073] (e) Carboxyl activation of carbon nanotubes

[0074] Take 50.2 mg of the quaternized carbon nanotubes (CNT-py-BHA) obtained in the above step (d), add it to 2 mL of anhydrous N,N-dimethylformamide (DMF) for ultrasonic dispersion, and then add 18.2 mg of N,N,N',N'-tetramethyl-O-(N-succinimidyl) urea tetrafluoroborate (TSTU) to obtain a suspension. After stirring the above suspension for 15 minutes, 10 μL of N,N-diisopropylethylamine is added, and the obtained solution is stirred for 8 hours to obtain a solution in which the carbon nanotube carboxyl group is activated;

[0075] (III) Synthesis of single atom catalysts

[0076] (f) Synthesis of single-atom site Os-N6 metal precursor

[0077] 324.4 mg of N,N'-dimethyl-2,2'-biimidazole and 439 mg of (NH4)2OsCl6 were poured into 12 mL of ethylene glycol solution respectively, and stirred at 140°C for 24 h under nitrogen protection to obtain a reaction mixture; 272.1 mg of N-(6-aminohexyl)-N'-methyl-2,2'-biimidazole was dissolved in 3 mL of ethylene glycol, and the solution was introduced into the above reaction mixture with a syringe, and continued to heat and stir at 160°C for 24 h under nitrogen protection to obtain a mixture, and the above mixture was cooled to room temperature, filtered to remove the precipitate, A filtrate is obtained, and the filtrate is diluted with 60 mL of water, and then mixed with 12 mL of AG1×4 resin chloride, and the mixture is stirred in an exposed conical flask for 48 hours to completely oxidize the Os(Ⅱ) complex to the Os(Ⅲ) complex, and the solution after the reaction is slowly poured into the NH4PF6 solution and stirred rapidly, and then filtered and collected by suction through a sintering funnel to obtain a crude product, and the crude product is ultrasonically dissolved again in 10 mL of acetonitrile, and centrifuged to obtain a clear liquid, and the obtained clear liquid is added to the NH4PF6 solution, and the NH4PF6 solution is prepared by dissolving 1.05 g of NH4PF6 in 50 mL of water. After the precipitation is generated again, the precipitate is collected by suction filtration, and then washed with pure water to obtain a solid, and the solid is dried at a temperature of 70°C for 24 hours in a vacuum drying oven with a vacuum degree of -0.1 MPa to obtain a single-atom site Os-N6 metal precursor;

[0078] (g) Synthesis of single atom catalysts

[0079] Take 330 mg of the single-atom site Os-N6 metal precursor in step (f), slowly add it to the carbon nanotube carboxyl-activated solution in step (e), and then add 40 μL of N,N-diisopropylethylamine. After stirring the mixture at room temperature for 24 hours, filter it, and wash the obtained precipitate with deionized water until the filtrate is colorless. The washed precipitate is dried in a vacuum drying oven with a vacuum degree of -0.1 MPa at a temperature of 70°C for 24 hours to obtain a single-atom catalyst;

[0080] (h) Purification of single atom catalysts

[0081] The single atom catalyst obtained in step (g) was dissolved in 20 mL of water, and then mixed with 4 mL of AG1×4 chloride resin, stirred in a beaker for 24 h, filtered to remove the resin, and rotary evaporated to obtain (CNT-Os6N) solid, which was dried at a temperature of 68-72° C. for 24 h to obtain a purified single atom catalyst;

[0082] (IV) Preparation of Glucose Electrochemical Working Electrode

[0083] (i) Preparation of sensor layer modification solution

[0084] The purified single-atom catalyst obtained in step (h) is dissolved in water to obtain a 10 mg / mL aqueous solution of the purified single-atom catalyst, 10 μL of the aqueous dispersion of the purified single-atom catalyst, 7 μL of a 10 mg / mL aqueous solution of glucose oxidase, 1.7 μL of a 10 mg / mL aqueous solution of polyethylene glycol diglycidyl ether and 31.3 μL of water are mixed, and the mixture is treated with ultrasound for 30 min, and then cross-linked at room temperature for 60 min to obtain a sensing layer modification solution;

[0085] (j) Electrode surface modification

[0086] The sensing layer modification solution was dropped onto the electrode surface. After the surface of the electrode was fully covered, the electrode was placed in a constant temperature and humidity incubator at 36° C. for 20 hours to obtain a working electrode.

[0087] The ultrasonic wave mentioned above is an ultrasonic cleaning machine operating at a frequency of 40KHz.

[0088] A single-atom glucose electrochemical working electrode is prepared by using the preparation method of the single-atom glucose electrochemical working electrode.

[0089] The working electrode obtained above was subjected to cyclic voltammetry test. The working electrode was placed in 1XPBS buffer solution manufactured by Shanghai Shenggong and scanned at a scan rate of 20mV / s, 50mV / s, 100mV / s, 200mV / s, 300mV / s, 400mV / s or 500mV / s to obtain the following Figure 1The cyclic voltammetry curve shown in FIG. 1 shows that below -200 mV, the redox peak of the electrode is lower than the voltage required for the catalytic oxidation of ascorbic acid, uric acid and acetaminophen interfering substances, and the electrode has good anti-interference ability.

[0090] The working electrode obtained above was subjected to chronoamperometry test. The working electrode was placed in 2 mM, 5 mM, 8 mM, 11 mM, 15 mM, 20 mM, 25 mM and 30 mM concentration glucose solutions, respectively. Figure 2 The chronoamperometric curve shown in the figure is used to record the current signal of the working electrode and obtain the following Figure 3 The linear relationship coefficient R between the current signal and the glucose concentration is shown 2 It is 0.99, indicating that the working electrode has a good linear response to glucose concentration.

[0091] The above embodiments are only used to help understand the method and core idea of ​​the present invention, and are not intended to limit the scope of the present invention. For those skilled in the art, the present invention may have several improvements and modifications. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of patent protection of the present invention.

Claims

1. A method for preparing a single-atom glucose electrochemical working electrode, comprising the following steps: (I) Pyridylation of carbon nanotubes (a) Purification of carbon nanotubes (CNT) First, the carbon nanotubes are dispersed in a concentrated hydrochloric acid solution with a concentration of 8-12 mol / L and soaked for 18-30 hours, and then refluxed in the concentrated hydrochloric acid solution for 4-6 hours, and then the carbon nanotubes are washed with water, ethanol and acetone in sequence until the pH of the washing solution is 7, and then the obtained solid is dried in a vacuum drying oven at a vacuum degree of -0.1 MPa and a temperature of 70°C for 18-30 hours to obtain purified carbon nanotubes CNT; (b) Preparation of diazonium salt Dissolve 1 part of sodium nitrite in 1.5-2 parts of water, and dissolve 1-1.5 parts of 4-aminopyridine in 1-1.2 parts of 3-5 mol / L hydrochloric acid, then mix the two solutions in an ice water bath and stir for 30-60 minutes to obtain a mixed solution of sodium nitrite and 4-aminopyridine; (c) Pyridyl modification of carbon nanotubes CNT-py 90-110 mg of the purified carbon nanotubes in step (a) are dispersed in 190-210 mL of N,N-dimethylformamide DMF, and dispersed under ultrasound for 50-150 min to obtain a solution of purified carbon nanotubes, and then the solution of purified carbon nanotubes is cooled to 0°C, and then 11-15 ml of a mixed solution of sodium nitrite and 4-aminopyridine obtained in the above step (b) is added dropwise to the solution of purified carbon nanotubes, first stirred at 0°C for 2-4 h, and then stirred at room temperature for 12-16 h, filtered and collected the obtained product, and then washed with 2 mol / L hydrochloric acid, 2 mol / L sodium hydroxide, water and acetone in sequence to remove impurities on the obtained product, so that the pH of the washing solution is 7, and finally the solid obtained after washing is placed in a vacuum drying oven with a vacuum degree of -0.1 MPa, and dried at 70°C for 18 to 30 h to obtain pyridine-modified carbon nanotubes CNT-py; (II) Quaternization modification of carbon nanotubes and carboxyl activation (d) Carbon nanotube quaternization CNT-py-BHA Take 75-80 mg of pyridine-modified carbon nanotubes CNT-py obtained in the above step (c) and add them to 1.8-2.2 mL of anhydrous N,N-dimethylformamide DMF for ultrasonic dispersion, then add 20-25 mg of 6-bromohexanoic acid 6-BHA, stir the solution at 90° C. for 20-26 h, and after the solution is cooled to room temperature, slowly pour it into 18-22 mL of ethyl acetate solution and stir it quickly, filter to obtain a solid, and dry the solid in a vacuum drying oven with a vacuum degree of -0.1 MPa at a temperature of 70° C. for 18 to 30 h to obtain quaternary ammonium-modified carbon nanotubes CNT-py-BHA; (e) Carboxyl activation of carbon nanotubes Take 50-52 mg of the quaternized carbon nanotube CNT-py-BHA obtained in the above step (d), add it to 1.8-2.2 mL of anhydrous N,N-dimethylformamide DMF for ultrasonic dispersion, and then add 17.5-19 mg of N,N,N',N'-tetramethyl-ON-succinimidyl urea tetrafluoroborate TSTU to obtain a suspension, stir the above suspension for 10-20 min, then add 8-12 μL of N,N-diisopropylethylamine, and stir the obtained solution for 7-9 h to obtain a solution of carbon nanotube carboxyl activation; (III) Synthesis of single atom catalysts (f) Synthesis of single-atom site Os-N6 metal precursor 320-330 mg of N,N'-dimethyl-2,2'-biimidazole and 430-440 mg of (NH4)2 OsCl6 were poured into 11-13 mL of ethylene glycol solution respectively, and stirred at 135-145°C for 22-26 h under nitrogen protection to obtain a reaction mixture; 270-278 mg of N-6-aminohexyl-N'-methyl-2,2'-biimidazole was dissolved in 2.5-3.5 mL of ethylene glycol, and the solution was introduced into the above reaction mixture with a syringe, and heated and stirred at 160°C for 20-26 h under nitrogen protection to obtain a mixture, and the above mixture was cooled to room temperature, filtered to remove the precipitate, and a filtrate was obtained, and the filtrate was diluted with 55-65 mL of water, and then mixed with 11-13 mL of AG1-×4 resin chloride, and the mixture was stirred in an open-mouth conical flask for 40-50 h, completely oxidize the OsⅡ complex to OsⅢ complex, slowly pour the reaction solution into NH4PF6 solution and stir rapidly, filter and collect the precipitate through a sintering funnel to obtain a crude product, re-dissolve the crude product in 8-12mL acetonitrile by ultrasonic, centrifuge to obtain a clear solution, add the obtained clear solution to NH4PF6 solution, the NH4PF6 solution is prepared by dissolving 1.0-1.1g NH4PF6 in 50mL water, collect the precipitate by suction filtration after precipitation is generated again, and then wash with pure water to obtain a solid, dry the solid in a vacuum drying oven with a vacuum degree of -0.1MPa at a temperature of 70°C for 20-26h to obtain a single-atom site Os-N6 metal precursor; (g) Synthesis of single atom catalysts Take 320-340 mg of the single-atom site Os-N6 metal precursor in step (f), slowly add it to the carbon nanotube carboxyl activated solution in step (e), and then add 35-45 μL of N, N-diisopropylethylamine, stir the mixture at room temperature for 20-26 hours, filter it, wash the obtained precipitate with deionized water until the filtrate is colorless, and dry the washed precipitate in a vacuum drying oven with a vacuum degree of 0.1 MPa at a temperature of 70°C for 20-26 hours to obtain a single atom catalyst; (h) Purification of single atom catalysts The single atom catalyst obtained in step (g) is dissolved in 18-22 mL of water, and then mixed with 3-5 mL of AG1-×4 chloride resin, stirred in a beaker for 22-26 h, filtered to remove the resin, and rotary evaporated to obtain CNT-OsN6 solid, which is dried at a temperature of 68-72 ° C for 20-25 h to obtain a purified single atom catalyst; (IV) Preparation of Glucose Electrochemical Working Electrode (i) Preparation of sensor layer modification solution The purified single-atom catalyst obtained in step (h) is dispersed in water to obtain a 9-11 mg / mL aqueous solution of the purified single-atom catalyst, 9-11 μL of the aqueous solution of the purified single-atom catalyst, 6-8 μL of a 9-11 mg / mL aqueous solution of glucose oxidase, 1.5-1.8 μL of a 9-11 mg / mL aqueous solution of polyethylene glycol diglycidyl ether, and 30-32 μL of water are mixed, and the mixture is treated with ultrasound for 20-40 min, and then cross-linked at room temperature for 50-70 min to obtain a sensing layer modification solution; (j) Electrode surface modification The sensing layer modification solution is dropped onto the electrode surface. After the surface of the electrode is fully covered, the electrode is placed in a constant temperature and humidity incubator at 34-37° C. for 18-24 hours to obtain a working electrode.

2. The method for preparing the single-atom glucose electrochemical working electrode according to claim 1, characterized in that: The ultrasonic wave is produced by an ultrasonic cleaning machine operating at a frequency of 40 KHz.

3. The method for preparing the single-atom glucose electrochemical working electrode according to claim 2, characterized in that: The working electrode is scanned in a buffer solution at a scan rate of 20 mV / s, 50 mV / s, 100 mV / s, 200 mV / s, 300 mV / s, 400 mV / s or 500 mV / s to obtain a cyclic voltammetry curve.

4. The method for preparing the single-atom glucose electrochemical working electrode according to claim 3, characterized in that: The working electrodes were placed in glucose solutions with concentrations of 2 mM, 5 mM, 8 mM, 11 mM, 15 mM, 20 mM, 25 mM and 30 mM, respectively.

5. The method for preparing the single-atom glucose electrochemical working electrode according to claim 4, characterized in that: The buffer solution is a PBS buffer solution.

6. A single-atom glucose electrochemical working electrode made by the preparation method of the single-atom glucose electrochemical working electrode according to claim 5.

Citation Information

Patent Citations

  • Working electrode of glucose monitoring probe and its fabrication method

    CN111248924B

  • Glucose electrochemical sensor and preparation method thereof

    CN112067671A

  • Transition metal complexes with bidentate ligand having an imidazole ring

    US7090756B2

  • Compositions of high specific activity Sn-117m and methods of preparing the same

    CN102326210A

  • Conductive nano-material glucose sensing material as well as preparation method and application thereof

    CN114384135A